LA ARQUITECTURA EN EL BELÉN DE SALZILLO - De la Peña Velasco, Concepción (Imafronte, 1999)
Scholarly works on Salzillo’s crih have concentrated primarily on the figures only touching on the architecture which includes a variety of examples. ranging from fhe tradifional to the courtly from the spanish to the europeati. The factors which influenced the design of the diferent biblical scenes; the location of the buildings in a non-urban contexr; the care for the external appearance. its decorafion and the suggestion of infernal spaces, including furniture and other objects that, in general, have not been conserved, the relationship of fhe figurines with the architecture have all been analysed in this paper.